Freshwater ascomycetes: Lophiostoma vaginatispora comb. nov. (Dothideomycetes, Pleosporales, Lophiostomaceae) based on morphological and molecular data - Zhang, Huang; Hyde, Kevin D.; Zhao, Yongchang; Mckenzie, Eric H.c.; Zhou, Dequn (Phytotaxa, 2014)
Lophiostoma vaginatispora comb. nov. was collected from submerged wood in a stream in Northern Thailand. The species is characteristic by immersed to erumpent ascomata, with slot-like ostioles, with long, branched and numerous periphyses, an unequally thick peridium where the upper part is narrower than the lower part, and 1-septate, narrowly fusiform ascospores with a thick surrounding papilionaceous sheath. The placement of this species in Lophiostoma is based on morphological characters and phylogenetic analyses of the partial nuclear ribosomal 18S small subunit and 28S large subunit DNA sequence data. Lophiostoma vaginatispora is distinguished from other Lophiostoma species in possessing a wide papilionaceous sheath.